2014
DOI: 10.1002/2013jd019912
|View full text |Cite
|
Sign up to set email alerts
|

Estimating global black carbon emissions using a top‐down Kalman Filter approach

Abstract: [1] Black carbon (BC) is an important aerosol constituent in the atmosphere and climate forcer. A good understanding of the radiative forcing of BC and associated climate feedback and response is critical to minimize the uncertainty in predicting current and future climate influenced by anthropogenic aerosols. One reason for this uncertainty is that current emission inventories of BC are mostly obtained from the so-called bottom-up approach, an approach that derives emissions based on categorized emitting sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
163
3

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(177 citation statements)
references
References 69 publications
11
163
3
Order By: Relevance
“…MAM4 shows a better agreement with the HIPPO measurements compared with MAM3 (Tilmes et al, 2015); however, the magnitude is still too low. This could be attributed to the underestimation of BC emissions in East Asia in the IPCC AR5 emission inventory used in CAM5 (Lamarque et al, 2010), as reported by previous studies (e.g., Cohen and Wang, 2014). We also find that the simulated aerosol layers are at higher altitudes than the observations.…”
Section: Comparison With In Situ Observationssupporting
confidence: 81%
See 2 more Smart Citations
“…MAM4 shows a better agreement with the HIPPO measurements compared with MAM3 (Tilmes et al, 2015); however, the magnitude is still too low. This could be attributed to the underestimation of BC emissions in East Asia in the IPCC AR5 emission inventory used in CAM5 (Lamarque et al, 2010), as reported by previous studies (e.g., Cohen and Wang, 2014). We also find that the simulated aerosol layers are at higher altitudes than the observations.…”
Section: Comparison With In Situ Observationssupporting
confidence: 81%
“…However, similarly to other global models , CAM5 significantly underestimates the nearsurface BC concentrations in remote regions, e.g., in the Arctic Wang et al, 2013;Ma et al, 2013a). While the underestimation of BC emission in Asia (e.g., Cohen and Wang, 2014) and in the high latitudes of the Northern Hemisphere (NH) (e.g., Stohl et al, 2013) can be an important factor, the excessively efficient scavenging of BC by liquid cloud processes (Wang et al, 2013) and the coarse horizontal resolution (∼ 100-200 km) of the model (Ma et al, 2014) also contribute to this model bias.…”
Section: Liu Et Al: Four-mode Version Of Modal Aerosol Modulementioning
confidence: 62%
See 1 more Smart Citation
“…One reason for the uncertainty is from the biases of current emission inventories of BC, mostly obtained from the so-called bottom-up approach (Cohen and Wang, 2014). Cohen and Wang (2014) provided a global-scale top-down estimation of BC emissions, a factor of more than 2 higher than commonly used global BC emissions data sets, by using a Kalman Filter method. If present-day BC emissions have been substantially underestimated, increase in aerosol net cooling effect may be larger due to only reduction in BC emission.…”
Section: Discussionmentioning
confidence: 99%
“…However, the diversity in existing estimates of the climate effect of BC is large (Bond et al, 2013;Boucher et al, 2013;Myhre et al, 2013). The causes for the diversity in estimates are many, from emissions (Amann et al, 2013;Cohen and Wang, 2014;Lam et al, 2012;Stohl et al, 2013;Wang et al, 2014b), lifetime and abundance (Hodnebrog et al, 2014;Samset et al, 2014;Wang et al, 2014a) to radiative efficiency Zarzycki and Bond, 2010).…”
Section: Introductionmentioning
confidence: 99%